Edge-nitrogenated biochar for efficient peroxydisulfate activation: An electron transfer mechanism - Wang, Huazhe; Guo, Wanqian; Liu, Banghai; Wu, Qinglian; Luo, Haichao; Zhao, Qi; Si, Qishi; Sseguya, Fred; Ren, Nanqi (Water research (Oxford), 2019)
N-doped biochars (NBCs) were prepared by pyrolyzing corncob biomass and urea in different proportion which manifested superior catalytic performance of peroxydisulfate (PDS) activation for sulfadiazine (SDZ) degradation. Through both dynamic fitting and density functional theory (DFT) calculations, the critical role of edge nitrogenation in biochar (BC) structure was revealed for the first time. The incorporation of edge nitrogen configurations (pyridinic N and pyrrolic N rather than graphitic N) generated reactive sites for the PDS activation. Additionally, a thorough investigation was conducted to explicate the PDS activation mechanism by NBC through chemical quenching experiments, electron spin resonance (ESR) detection, oxidant consumption monitoring and electrochemical analysis. Different from the well-reported singlet oxygen (1O2) dominated nonradical mechanism, an electron transfer pathway involving surface-bound reactive complexes was proved to play a major role in the NBC/PDS system. Benefit from the electron transfer mechanism, the NBC/PDS system not only has wide pH adaptation for real application, but also shows high resistance to the inorganic anions in aquatic environment. We believe this study will deepen the understanding of the carbon-driven persulfate activation mechanism and provide strong technical support for the BC-mediated persulfate activation in practical applications. [Display omitted] •N-doped biochars exhibited superior performance towards peroxydisulfate activation.•Edge nitrogenation disturbed the electron density and created reactive sites.•Electron transfer pathway rather than singlet oxygen dominated in the redox system.•Negative effect of anions was suppressed by the electron transfer mechanism.